An elevated lipoprotein(a) plasma level as a cardiovascular risk factor. (May 2015) - Tselmin, S.; Müller, G.; Gelgaft, E.; Fischer, S.; Julius, U.
Abstract: Introduction: The causal association of elevated lipoprotein(a) (Lp(a)) plasma levels with the increased cardiovascular risk is still controversial and presently there are no standard recommendations on managing of hyperLp(a)emia. Our retrospective analysis is aimed to explore the Lp(a) thresholds, the magnitude of various cardiovascular risk factors and their combinations. Methods: The files of 544 outpatients from our Outpatient Department of Lipid Disorders were divided into quintiles with respect to Lp(a) levels and reviewed regarding age, gender, Body Mass Index, dyslipidemias, arterial hypertension, diabetes mellitus, smoking and incidence of vascular events in coronaries, carotids and lower extremities. Furthermore we built 15 small quantiles to identify the Lp(a) threshold more precisely. Results: The incidence odds ratio for cardiovascular events rose from 2.65 in the 2nd quintile with Lp(a) 483–821 mg/L to 6.36 in the 5th quintile (Lp(a) ≥ 1495 mg/L). The relative risk of cardiovascular events was 0.08 in subjects with a Lp(a) level under 232 mg/l and 3.6 at Lp(a) ≥ 315 mg/L. The magnitude of the combination of elevated Lp (a) with arterial hypertension factor exceeded that of gender, age and combination of arterial hypertension with smoking. Conclusions: A Lp(a) plasma level of higher than about 300 mg/L seems to be a threshold for occurring of cardiovascular events. The combination of raised Lp(a) with arterial hypertension was found to be the most important cardiovascular risk factor. Lp(a) levels under 232 mg/L appeared to be a marker for good prognosis.